Techniques in Group Counseling to Develop Student Career Maturity: Systematic Literature Review - Pranowo, Taufik Agung; Jana, Padrul; Azman, Mohamed Nor Azhari; Kassymova, Gulzhaina; Kurniawan, Drajat Edy; Febrianto, Arip (Kuras Institute, 2024)
This article presents an in-depth review of how group counseling, with an emphasis on mindfulness techniques and the impact of technology, plays a role in improving Student Career Maturity. Career maturity involves a deep understanding of career goals, the ability to manage challenges, and a willingness to continuously learn and develop. In this context, mindfulness techniques can be considered as an effective alternative tool for increasing career maturity. Mindfulness techniques have become a key element in this group counseling process. This research method uses Literature Study. The total number of articles used was 200 articles, divided according to the objectives of this research. Topics discussed, including group counseling, the use of technology in career development and student career maturity and obtained a total of 45 articles. Data extraction is carried out by preparing space to record information or sources. Data synthesis is carried out by summarizing and synthesizing these findings. The results obtained in this review, that the concept of career maturity can consider mindfulness techniques and the impact of technology in group counseling, and provide insight into how the integration of these two elements can provide real benefits in increasing students' career maturity. The development of information and communication technology has opened access to various sources of information and tools that can support the career counseling process. The use of online platforms, online resources, and technology-enabled counseling applications provides opportunities to provide more effective and affordable counseling services. In conclusion, group counseling with mindfulness techniques and the use of technology is a powerful tool in helping students develop their career maturity in this modern era.